Laser‐Printed, Flexible Graphene Pressure Sensors (Global Challenges 4/2020) - Kaidarova, Altynay (Glob Chall, 2020)
In article number https://doi.org/10.1002/gch2.202000001, Jurgen Kosel and co‐workers design a wearable, flexible piezoresistive graphene sensor by a facile, one‐step laser‐printing fabrication process. The sensors feature long‐term stability, biocompatibility, and a low detection limit in combination with an extensive dynamic range. They can function as wearable artificial skins, monitors for heart rate or plantar pressure, or provide a tactile sense. They can also be employed in harsh environments. [Image: see text]